1995
DOI: 10.1017/s002202990003363x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forage digestibility and type of concentrate on nutrient utilization by lactating dairy cattle

Abstract: SummarySix lactating dairy cows were used in a three period, part balanced changeover design experiment to investigate the effects of forage digestibility and concentrate composition on the efficiency of nutrient utilization in lactating dairy cows. Six treatments comprising three forage regimens and two concentrate types (starch υ. fibre) were examined in a 3 × 2 factorial design. The three forage regimens were high digestibility grass silage offered ad lib. (HA) or restricted to 6·5 kg dry matter/d (HR) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 9 publications
3
33
1
Order By: Relevance
“…On the contrary, 22 out of 31 studies [8, 9, 15, 60, 61, 63-65, 67, 68, 78, 82, 99-107] reported a decrease in DMI after feeding extra lipogenic nutrients compared to 7 out of 14 studies [60,61,68,72,77,78,[108][109][110][111][112][113][114][115][116] on extra glycogenic nutrients which showed a decrease in DMI in the treatment group. In general, the negative effect of extra lipogenic sources on dry matter intake is higher when the degree of saturation of fatty acids is lower, probably because of the more pronounced negative effects of unsaturated fatty acids on rumen carbohydrate fermentation.…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Energy Intakementioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, 22 out of 31 studies [8, 9, 15, 60, 61, 63-65, 67, 68, 78, 82, 99-107] reported a decrease in DMI after feeding extra lipogenic nutrients compared to 7 out of 14 studies [60,61,68,72,77,78,[108][109][110][111][112][113][114][115][116] on extra glycogenic nutrients which showed a decrease in DMI in the treatment group. In general, the negative effect of extra lipogenic sources on dry matter intake is higher when the degree of saturation of fatty acids is lower, probably because of the more pronounced negative effects of unsaturated fatty acids on rumen carbohydrate fermentation.…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Energy Intakementioning
confidence: 99%
“…Eight of the 12 studies reported an increase in EB after feeding extra lipogenic nutrients [8, 9, 12, 15, 64,66,106]. In contrast to feeding extra glycogenic nutrients where 12 out of 13 studies were able to improve, not-significantly, the calculated EB [66,69,71,72,77,107,108,110,112,116,120].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Ebmentioning
confidence: 99%
“…November 2010 to January 2011 and January 2012 to March 2012), by releasing known quantities of standard CO 2 , CH 4 and N 2 (used to reduce O 2 concentration) into the chambers. All equipment, procedures, analytical methods, and calculations used in the calorimetric study were as reported by Gordon et al (1995).…”
Section: Calorimetersmentioning
confidence: 99%
“…Animals were then housed in calorimeter chambers for 3 to 5 days with measurement of total gaseous exchange (CH 4 , CO 2 and O 2 ) taking place during the final 2 to 4 days. All equipment, sampling procedures, analytical methods and calculations used in the calorimetric studies were described by Gordon et al (1995) and calibration of the chambers by Yan et al (2000). Energy corrected milk yield (ECMY) was calculated from measured milk energy output (E l , MJ/day) divided by the calculated energy concentration (MJ/kg) of 1 kg of standard milk (concentrations of fat, protein and lactose = 40, 32 and 48 g/kg, respectively).…”
Section: Animals and Cow Genetic Meritmentioning
confidence: 99%